2019
DOI: 10.1021/acs.iecr.9b01209
|View full text |Cite
|
Sign up to set email alerts
|

Small-Size Polymerase Chain Reaction Device with Improved Heat Transfer and Combined Feedforward/Feedback Control Strategy

Abstract: We report improvements on the heat transfer and on the control strategy of a thermal cycler implemented on a novel device for performing a fast polymerase chain reaction (PCR). The reduction of the thermal mass of the sample holder and the direct contact with the sample allow for a significant reduction of the transition times, while the hybrid feedforward/feedback controller can rely on inexpensive components (actuators, sensors, processor) and still achieve minimal over/undershooting and good temperature sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…To further simplify, decentralize, and speed up the process of VOC identification, we transformed our assay to a portable and inexpensive qPCR device, named peakPCR . 16 The device can complete up to 20 RT-qPCR reactions in less than 40 min. Important characteristics of peak PCR are the relatively low cost of production and the simplicity of usage.…”
Section: Introductionmentioning
confidence: 99%
“…To further simplify, decentralize, and speed up the process of VOC identification, we transformed our assay to a portable and inexpensive qPCR device, named peakPCR . 16 The device can complete up to 20 RT-qPCR reactions in less than 40 min. Important characteristics of peak PCR are the relatively low cost of production and the simplicity of usage.…”
Section: Introductionmentioning
confidence: 99%
“…One research group optimized the heat transfer to achieve fast thermal cycling with the use of a sample holder that quickly dissipated excess heat due to its high thermal conductivity. The significant reduction of the transition times (68% compared to commercial real-time PCR) leads to an increased speed of amplification [58]. A different approach to speed up PCR is the use of induction heating [59].…”
Section: Discussionmentioning
confidence: 99%
“…The temperature profile indicated that the chip temperature can reach ~62 °C within 17 s and then fluctuated slightly between 61.8 and 63.6 °C, and this is an acceptable fluctuation range for LAMP amplification. Compared with the contact-type hot-plate heating method widely used in commercial instruments, this non-contact LED-driven heating solution no longer requires the hot cover for reducing the temperature difference between the hot plate and the chip [29]. This is because AuNPs can efficiently and directly convert the energy from the NIR-LED source into heat of the PDMS film.…”
Section: Photothermal Performancementioning
confidence: 99%
“…During droplet generation, the flow rate of the oil phase and the LAMP reagent was 12 and 6 μL/min, respectively, so it takes ~4 min to complete sample segmentation of 20 μL of LAMP reagent. The droplet size profile is of great value for characterizing the sample Compared with the contact-type hot-plate heating method widely used in commercial instruments, this non-contact LED-driven heating solution no longer requires the hot cover for reducing the temperature difference between the hot plate and the chip [29]. This is because AuNPs can efficiently and directly convert the energy from the NIR-LED source into heat of the PDMS film.…”
Section: Performance Characterization Of Digital Lamp Chipmentioning
confidence: 99%